2014
DOI: 10.1371/journal.pone.0093565
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Mapping between Non-Symbolic and Symbolic Numerical Magnitudes and Its Association with Timed and Untimed Tests of Mathematics Achievement

Abstract: The ability to map between non-symbolic numerical magnitudes and Arabic numerals has been put forward as a key factor in children’s mathematical development. This mapping ability has been mainly examined indirectly by looking at children’s performance on a symbolic magnitude comparison task. The present study investigated mapping in a more direct way by using a task in which children had to choose which of two choice quantities (Arabic digits or dot arrays) matched the target quantity (dot array or Arabic digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 30 publications
8
67
2
Order By: Relevance
“…This suggests there is an additional cost to translating between the two formats. This result is broadly consistent with those found by Mundy andGilmore (2009) andBrankaer et al (2014). Mundy and Gilmore found in their second experiment that children roughly 7-8 years of age struggled with a mapping task (children judged which of two quantities matched the numerosity of a target, where the target was in a different format -symbolic or nonsymbolic -from that of the two options): Average accuracy was 62% (chance=50%).…”
Section: Evidence For the Sns→ams Viewsupporting
confidence: 89%
See 1 more Smart Citation
“…This suggests there is an additional cost to translating between the two formats. This result is broadly consistent with those found by Mundy andGilmore (2009) andBrankaer et al (2014). Mundy and Gilmore found in their second experiment that children roughly 7-8 years of age struggled with a mapping task (children judged which of two quantities matched the numerosity of a target, where the target was in a different format -symbolic or nonsymbolic -from that of the two options): Average accuracy was 62% (chance=50%).…”
Section: Evidence For the Sns→ams Viewsupporting
confidence: 89%
“…More recently, Brankaer et al (2014) found a highly similar result using similar matching and comparison tasks in children approximately 7 and 9 years old.…”
Section: Evidence For the Sns→ams Viewmentioning
confidence: 62%
“…Similarly Brankaer, Ghesquière, and De Smedt (2014) found that children's performance on a similar mapping task developed from age 6 to 8 and was related to performance on both timed and untimed mathematics tests, after controlling for magnitude comparison performance. These findings concur with data from Booth and Siegler (2008), which showed a relationship between children's ability to map symbolic Running head: PRESCHOOL MAGNITUDE REPRESENTATIONS 6 representations onto a number line and later arithmetical achievement.…”
Section: Magnitude Representations and Mathematicsmentioning
confidence: 79%
“…Similarly Brankaer, Ghesquière, and De Smedt (2014) found that children's performance on a similar mapping task developed from age 6 to 8 and was related to performance on both timed and untimed mathematics tests, after controlling for magnitude comparison performance. These findings concur with data from Booth and Siegler Alternatively, the symbolic system may be acquired independently of the nonsymbolic system and the mapping between nonsymbolic and symbolic representations might occur later, once children have acquired the symbolic system (e.g., Le Corre & Carey, 2007).…”
Section: Magnitude Representations and Mathematicsmentioning
confidence: 82%
“…Indeed, children’s exact number abilities – especially those related to their emerging understanding of exact number symbols – have also been shown to be important for math achievement. For example, Holloway and Ansari (2009), Brankaer and colleagues (2014), and Sasanguie and colleagues (Sasanguie et al, 2012; Sasanguie, Defever, Maertens, & Reynvoet, 2013) found that children’s performance on a symbolic number comparison task (e.g., showing participants two Arabic numerals and asking them to quickly judge which is greater) correlated with math abilities. Similarly, Kolkman and colleagues (2013) found that kindergarteners’ performance on a symbolic number comparison task and a symbolic number line estimation task (but not on a non-symbolic number comparison task or a non-symbolic number line estimation task) predicted math performance in first grade.…”
Section: Introductionmentioning
confidence: 99%